Measuring Quality for Public Reporting of Health Provider Quality: Making It Meaningful to Patients - Mukamel, Dana B. (American Public Health Association, 2010)
Public quality reports of hospitals, health plans, and physicians are being used to promote efficiency and quality in the health care system. Shrinkage estimators have been proposed as superior measures of quality to be used in these reports because they offer more conservative and stable quality ranking of providers than traditional, nonshrinkage estimators. Adopting the perspective of a patient faced with choosing a local provider on the basis of publicly provided information, we examine the advantages and disadvantages of shrinkage and nonshrinkage estimators and contrast the information made available by them. We demonstrate that 2 properties of shrinkage estimators make them less useful than nonshrinkage estimators for patients making choices in their area of residence.